Medicago truncatula Natural Resistance-Associated Macrophage Protein1 Is Required for Iron Uptake by Rhizobia-Infected Nodule Cells . Issue 1 (27th March 2015) - Tejada-Jiménez, Manuel; Castro-Rodríguez, Rosario; Kryvoruchko, Igor; Lucas, M. Mercedes; Udvardi, Michael; Imperial, Juan; González-Guerrero, Manuel
Abstract : An Nramp-type transporter provides the cytosolic iron that is transferred to bacteroids for synthesis of ferroproteins involved in nitrogen fixation. Abstract: Iron is critical for symbiotic nitrogen fixation (SNF ) as a key component of multiple ferroproteins involved in this biological process. In the model legume Medicago truncatula, iron is delivered by the vasculature to the infection/maturation zone (zone II) of the nodule, where it is released to the apoplast. From there, plasma membrane iron transporters move it into rhizobia-containing cells, where iron is used as the cofactor of multiple plant and rhizobial proteins (e.g. plant leghemoglobin and bacterial nitrogenase). MtNramp1 ( Medtr3g088460 ) is the M. truncatula Natural Resistance-Associated Macrophage Protein family member, with the highest expression levels in roots and nodules. Immunolocalization studies indicate that MtNramp1 is mainly targeted to the plasma membrane. A loss-of-function nramp1 mutant exhibited reduced growth compared with the wild type under symbiotic conditions, but not when fertilized with mineral nitrogen. Nitrogenase activity was low in the mutant, whereas exogenous iron and expression of wild-type MtNramp1 in mutant nodules increased nitrogen fixation to normal levels. These data are consistent with a model in which MtNramp1 is the main transporter responsible for apoplastic iron uptake by rhizobia-infected cells in zone II.